SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN KREDIT PADA PT. BPR PIJER PODI KEKELENGEN DENGAN METODE (WEIGHTED PRODUCT ) WP - Jesika Br Sinulingga; Jenny Veronika Ginting (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
Credit is a financial facility that allows a person or business entity to borrow money to buy a product and repay it within a specified period. The provision of credit is the main activity of banks and finance companies (multi) which contain risks that can affect the health and business continuity of the bank. In giving credit to the right customers, because it has not been done computerized. To anticipate that there will be no difficulties, a Decision Support System is needed. One method that can be used for Decision Support Systems is to use a WP (Weighted Product). The research was conducted to find the weight value for each attribute, then carried out a ranking process that would determine the optimal alternative. The results of this study are more precise than the manual system used so far for creditworthiness